Performance of Structure Equipped AP-TMD Compared with MTMD, ATMD, and PTMD against Earthquake Using Genetic Fuzzy Algorithm - Hadizadeh, F.; Akhlaghi Amiri, F.; Shariatmadar, H. (Advances in Civil Engineering, 2022)
During the past years, different control devices have been introduced and used to reduce the response of structures. This article presents the performance of active-passive tuned mass dampers (AP-TMDs) in the reduction of structural responses and a comparison between the uses of different controllers, including tuned mass damper (TMD), active tuned mass damper (ATMD), and multituned mass damper (MTMD). Analyzing and modeling the structure under four near- and far-field earthquakes are performed in MATLAB and SIMULINK. Finally, the responses of controlled and uncontrolled structures equipped with these controllers are investigated. Fuzzy and genetic-based fuzzy logic controllers are used to determine the control force of ATMD and AP-TMD, respectively. In order to compare the performance of the dampers, the mass ratio of TMDs is fixed in all cases and is taken to be 5%. Damping of the structure is considered equal to 5%. The frequency and damping ratio of TMDs with maximum and RMS displacement optimization criteria are obtained. The mass ratio of TMDs in controlled structures with MTMD and AP-TMD is calculated by numerical analysis. It can be inferred that using control force affects response reduction in both ATMD and AP-TMD controllers significantly. In addition, using AP-TMD can bring the merits of both passive and active systems by providing active control and reducing power requirements for control forces. All controllers are recommended for structural control although AP-TMD reduced maximum and RMS displacement by about 50% in the best case, which has better performance than others. On the other hand, ATMD decreased RMS acceleration by 37.5% on average in four earthquakes compared to the uncontrolled structure.